Incidence, predictors, and timing of post-operative stroke following elective total hip arthroplasty and total knee arthroplasty - Haynes, Monique S. (PLoS One, 2020)
BACKGROUND: Postoperative stroke is a rare but potentially devastating complication following total hip arthroplasty (THA) and total knee arthroplasty (TKA). The purpose of the current study was to determine the incidence, independent risk factors, and timing of stroke following THA and TKA utilizing the National Surgical Quality Improvement (NSQIP) database. METHODS: Patients who underwent elective primary THA and TKA were identified in the 2005–2016 NSQIP database. Thirty-day postoperative strokes were identified, timing was characterized, and an incidence curve was created. Multivariate analyses determined the independent predictors of these strokes. RESULTS: Of 333,117 patients identified, 286 (0.09%) experienced a stroke. Given that THA vs TKA was not a univariate predictor of stroke, the two procedures were considered together. The majority (65%) of strokes occurred before discharge. Of the strokes observed, 25% occurred by postoperative day one, 50% by postoperative day two, and 75% by postoperative day nine. Independent risk factors for postoperative stroke were: age (60–69 years old odds ratio [OR] = 4.2; 70–79 years old OR = 8.1; ≤80 years old OR = 16.1), higher American Society of Anesthesiologists (ASA) score (ASA≥3 OR = 1.7), and smoking [OR = 1.6). CONCLUSION: The incidence of stroke after THA/TKA was low at 0.09%, with the majority occurring prior to discharge and half occurring by postoperative day two. Patients who were older, sicker, or who were smokers were at greater risk of postoperative stroke. These findings can be used to council patients and to optimize patient care. LEVEL OF EVIDENCE: Level III, Retrospective comparative study.